CTLA-4 expressing innate lymphoid cells modulate mucosal homeostasis in a microbiota dependent manner - Jonathan W. Lo; Jan-Hendrik Schroeder; Luke B. Roberts; Rami Mohamed; Domenico Cozzetto; Gordon Beattie; Omer S. Omer; Ellen M. Ross; Frank Heuts; Geraldine M. Jowett; Emily Read; Matthew Madgwick; et al. (Nature Communications)
Abstract The maintenance of intestinal homeostasis is a fundamental process critical for organismal integrity. Sitting at the interface of the gut microbiome and mucosal immunity, adaptive and innate lymphoid populations regulate the balance between commensal micro-organisms and pathogens. Checkpoint inhibitors, particularly those targeting the CTLA-4 pathway, disrupt this fine balance and can lead to inflammatory bowel disease and immune checkpoint colitis. Here, we show that CTLA-4 is expressed by innate lymphoid cells and that its expression is regulated by ILC subset-specific cytokine cues in a microbiota-dependent manner. Genetic deletion or antibody blockade of CTLA-4 in multiple in vivo models of colitis demonstrates that this pathway plays a key role in intestinal homeostasis. Lastly, we have found that this observation is conserved in human IBD. We propose that this population of CTLA-4-positive ILC may serve as an important target for the treatment of idiopathic and iatrogenic intestinal inflammation.